Introduction: The Politics of Open Access — Decolonizing Research or Corporate Capture?. Issue 2 (28th January 2021) - Meagher, Kate
ABSTRACT: This introductory article looks beyond the conventional framing of open access (OA) debates in terms of paywalls and copyrights, to examine the historical processes, institutional and digital infrastructures, and political dynamics shaping the effects of OA in development research. From a historical perspective, it focuses on tensions and crises in the relationship between scholarly and corporate publishing ecosystems. The spectrum of open access models is also examined, with a focus on green, gold, diamond and black, which tend to obscure the underlying scholarly publishing infrastructures that shape the parameters of openness and access. A closer look at distinctive for‐profit and non‐profit OA infrastructures reveals the inequitable and often neo‐colonial effects of for‐profit models on Southern researchers and the social sciences. Accounts of the politics of OA highlight processes of political capture of the OA agenda by Northern corporate and state interests and draw attention to alternative interest coalitions which are more suited to prioritizing the global public good over private profit. Reflecting on the requirements of OA in low‐resource environments, this article echoes calls for more equitable forms of openness and access in development research ecosystems, with a view to decolonizing as well as advancing OA.